Antibiotics Resistance Pattern of Staphylococcus aureus Isolated From In-patients of an Orthopaedic Hospital in North- Western Nigeria - Dominic Oche; Paul Oyegoke; Maryloveth Akpudo; Busayo Olayinka (Shahrekord University of Medical Sciences, 2021)
Background and aims: Staphylococcus aureus, an important pathogen in bone diseases, is a highly multi-drug resistant (MDR) bacterium. This study aimed to investigate the antibiotic resistance among S. aureus isolated from patients on admission in an orthopaedic hospital. Methods: In this cross-sectional research, 140 samples comprising urine samples, wound swabs, and nasal swabs were collected from 49 patients on admission. Samples were cultured and screened for S. aureus following standard procedures. Using the agar-disk diffusion method, the isolates were subjected to antibiotics susceptibility tests. Results: S. aureus were isolated from 26 (18.6%) samples, and wound swabs were found to have the highest number of the S. aureus isolates with 12 (46.2%). Among the 26 S. aureus isolated, 25 (96.2%) isolates were resistant to at least four or more of the tested antibiotics. There were 23 (88.5%) MDR isolates, while there were only 2 (7.6%) extensively drug resistant ones. The number of methicillin-resistant S. aureus were 17 (65.4% of the isolates), while the number of methicillin-susceptible S. aureus were 9 (34.6% of the isolates). A total of 22 (84.6%) isolates had multi-antibiotic resistance (MAR) index greater than 0.2. Inducible clindamycin resistance of 2 (7.6%) was observed. Conclusion: This study showed that the S. aureus isolated from the patients were resistant to multiple antibiotics. Regular surveillance of antibiotic resistance is of utmost importance, since it facilitates the design or development of the treatment regimens that could check the spread of antimicrobial resistance.